Persepsi Seonhohada di Indonesia Terkait Karakter Psikopat Kim Seon-Ho pada Film The Childe - Khoirunisa, Nadhira; Hidayanto, Syahrul (CV Widina Media Utama, 2025)
Film is a medium that has the power to transfer messages and values to a wide audience. The audience of the film is diverse and thanks to the diversity of its audience, film becomes a unique mass communication medium because it can create different perceptions among its viewers. The author chose the film The Childe as the object of research because the depiction of the psychopath character in the film The Childe is different from other films or series about psychopaths. This film depicts a psychopath as a figure who has empathy, looks neat with a suit and formal hairstyle. In addition, Kim Seon-Ho, one of the South Korean actors who is known for often playing the protagonist in films so that he is nicknamed